Faktor-faktor Risiko Stres Kerja pada Aparatur Sipil Negara - Bryan Reppi; Oksfriani Jufri Sumampouw; Hesty Lestari (Universitas Sam Ratulangi, 2020)
Background: The Health and Safety Executive (HSE) stated that stress and depression related to work in 2017/2018 were 595,000 cases with a prevalence rate of 1,800 per 100,000 workers. Work-related stress and depression also contribute 44% of all cases of occupational health disorders and 57% of absences from work due to illness. Job stress can occur to workers in all fields including government employees. This study aims to determine the relationship between risk factorsand work-related stress on civil servants in Regional Financial and Asset Agency of North Sulawesi Province.Â Method: This research was a quantitative study with cross sectional research design, conducted in 2019, from August to September at the Regional Finance and Assets Agency (BKAD) of North Sulawesi Province. The sample was 118 people determined by the Total Sampling method. Data was collected by respondent completing NIOSH Generic Job Stress Questionnaire. Univariate, bivariate, and multivariate were use to analyze the data using SPSS program. Results: The results showed that there was a relationship between interpersonal conflict, workload, social support and work stress on civil servants in BKAD North Sulawesi Province. Conclusion: This study concluded that interpersonal conflict is the most influential factor in work-related stress on civil servants in BKAD North Sulawesi Province. It is recommended for all civil servants in BKAD North Sulawesi Province to be more aware to the work-related stress factors so that it can be controlled